University students’ approaches to online learning technologies: The roles of perceived support, affect/emotion and self-efficacy in technology-enhanced learning - Han, Jiying; Geng, Xiaohui (Computers and education, 2023)
In the context of technology-enhanced learning (TEL), the quality of students' learning is determined largely by their use of online learning technologies. Building on the framework of students' approaches to learning, this study investigated students’ approaches to online learning technologies (SAOLT) in relation to their perceptions of support, affect/emotion and self-efficacy in online learning environments during the COVID-19 pandemic. Based on a questionnaire survey of 7210 Chinese undergraduate students, SEM analysis revealed that perceived instructional support was positively related to the deep approach to online learning technologies and negatively related to the surface approach to online learning technologies. Perceived peer support and technical support were indirectly related to the deep approach to online learning technologies, mediated by affect/emotion and self-efficacy. The findings deepen our understanding of SAOLT and yield pedagogical implications for efforts to promote a deep approach to online learning technologies, thus fostering high-quality learning in the context of TEL. •Instructional support was positively related to the deep approach.•Instructional support was negatively related to the surface approach.•Affect/emotion was positively related to both deep and surface approaches.•Self-efficacy was positively related to the deep approach.•Affect/emotion and self-efficacy mediated between perceived support and SAOLT.